RENEWABLE ENERGY SOURCES AND THE PROBLEM OF ENVIRONMENTAL PROTECTION - Kozyrskyi, Volodymyr; Martyniuk, Liliia (Енергетика і автоматика, 2016)
In this paper presents research results the environmental assessment of emissions of harmful substances into the air from burning fuel for electricity production process power plants RES. It is established that during the production of renewable energy systems pollute the environment. For general environmental assessment must take into account the environmental impact of power plants with the RES on the environment at all stages in the process of their production, use and disposal.